PHYSICO-CHEMICAL AND BACTERIOLOGICAL ANALYSIS OF SPRING WATERS IN ARGAO, CEBU - Pinote, Juanita P.; Alburo, Rosalyn P.; Alburo, Hemres M.; Cutillas, A L. (Journal of Agriculture and Technology Management, 2018)
Water is one of the most vital and peculiar substances on Earth. It is very essential that every individual have access to safe drinking water because it is a basic human right. Without water, nothing could live. A person takes about eight to 10 glasses of water daily. This study was conducted to determine the physico-chemical and bacteriological qualities of 15 spring water sources in Argao, Cebu using the Philippine National Standards for Drinking Water (PNSDW). Water samples were brought to a DOH accredited laboratory to analyze the following parameters namely; Total Dissolved Solids (TDS) and Total Suspended Solids (TSS) using Gravimetric method; pH using the Electrometric method; Salinity using Conductemetric method; Bicarbonates and Ca using Titration; Chlorides using Argentometric method; Mg by calculation; Na, Lead, and Mercury by AAS method; sulfates by Turbidimitric Method; zinc by Zircon Method and total hardness by EDTA Titrimetric Method. For Total Fecal Coliforms and E. coli, Multiple Tube Fermentation Technique was used. Results revealed that all the 15 water samples failed in Total Coliform and HPC test although it passed in the Fecal and E. coli test. Lead content is below the threshold level of 0.01 ppm. Seventy-seven per cent of the samples passed the standards while the rest failed. Overall results are alarming because communities derive their drinking water from these sources. It is deemed important that communities be educated on the proper care of their springs and the LGU to do periodic monitoring to prevent water-related diseases outbreaks.